Natural gas pricing GSA Bolivia-Brazil using virtual hub and expected monetary value instruments - Jorge L. Gumucio; Sergio M. Medinaceli (Institute for Advanced Development Studies (INESAD), 2019)
The purpose of this paper is to show the shortcomings of incentive policies, specifically competitiveness, if they are designed without considering fundamentals of market development such as, level of demand, level of investment, and availability of alternative sources of supply. We focus on the analysis of the main market, financial, and economic variables in the Bolivia-Brazil Gas Supply Agreement, their relationship, development and dynamics through time and the current situation before the contract is renegotiated in 2019. Our analysis centers on the effective negotiation margin that Bolivia has calculated from the overall production costs of Bolivian gas (using EMV) vis a vis the opportunity cost of Brazil importing LNG. Using 10%-15% as discount rates and WTI prices between 50 and 60/bbl, the natural gas price result of EMV is between 4.96 and 7.99/MMbtu. Using the Bolivian tax incentive gas price should be between 2.29 and 5.16/MMbtu. Under the assumptions that WTI levels would be around 60/bbl, investors use a 15% discount rate to invest in Bolivia, incentive policy is in place, and the price of LNG is around 6.84/MMbtu; the opportunity cost of Brazil importing gas from Bolivia is -0.55/MMbtu. The same case without incentive policy will yield a -3.38/MMbtu. On the other hand, if the transport tariff is reduced the margin becomes positive under the assumption that the incentive policy is still in place. Therefore, as the price of LNG becomes more competitive through increase in supply (worldwide), Brazil will set its negotiation position around the price that they could import LNG on the short to medium term.
Keywords: Q31; Q35; F15; 330; Netback prices; GSA; Gas Pricing; Gas Contract Negotiation; Virtual Hub; Expected Monetary Value